BUDAYA SUMATERA BARAT DAN PARIWISATA : BISAKAH FESTIVAL “TABUIK” DI PARIAMAN MENJADI DAYA TARIK WISATA INTERNASIONAL? - Ekasari, Rini (Jurnal Ilmiah Pariwisata, 2012)
Tourism has become one of the important industries in the world nowadays. It provides a major economic development opportunity for many countries and a means of improving the livelihoods of its residents. It is also considered as a reliable sector to improve the economic development in Indonesia. “Tabuik”festival in Pariaman is one of the cultural event which is promoted to be national tourism agenda and even it is now promoted internationally.This research is focused on the the potency of “Tabuik” as a cultural event in Pariaman to be developed as an international annual tourist attraction. In this research, the survey was conducted toward domestic tourists and local communities. Moreover, the interviews was also conducted to  international tourists for asking their their perception about this event. In order to know the effort of the local government to achive the goal, interview toward the head of Tourism Board of Pariaman and tourism actors was also done.For the local communities, “Tabuik” has 3 meanings, social, cultural and economic. Both, domestic and international tourists give positive perceptions on this event. Local government and communities also support “Tabuik” to be an international tourist attraction. However, there are still the obstacles to face such as lack of information toward the tourists, the insufficient infrastructures and facilities, inadequate fund, and the unreadiness in the development of tourism. The form of unreadiness are the denial toward tourism from the local people and unsmooth social structure in implementing strategic role.The local government has been doing some efforts to make “Tabuik” and Pariaman to be an international destination. The improvement of all destinations in Pariaman is always be the priority. The local government  also tries to invite the investors to make investment in private sector of tourism. To promote “Tabuik” internationally, the local government has been trying an attempt by following the international tourism event. Besides, the local government has set up “Rumah Tabuik” ; a kind of building whose function as a place to make Tabuik and as “Tabuik” museum. Hopefully, this thesis is beneficial for the improvement of tourism in Pariaman West Sumatera in the future